Cara Mendidik Anak Dalam Islam - Mardiah Astuti; Herlina Herlina; Ibrahim Ibrahim; Cahyadi Cahyadi; Nabila Kontesa; Nyimas Andini; Rafa Nabila (Jurnal Riset Rumpun Agama dan Filsafat, 2023)
The way children are educated in Islam has an impact on their growth and role in life. Through this article, we examine the factors that cause the success of how to educate children in Islam focusing on the morals, manners and knowledge of children in the realm of the family. The type of analysis used in this study is literature search, or in other words called literature search. It is a problem-solving activity based on a critical and in-depth analysis of important library materials. Most of this research is done in newspapers and news stories, looking for different sources of information relating to the issue under investigation. This research method uses qualitative descriptive methods. The data displayed is categorized, displayed, and analyzed using a system of elaboration of the source's answers, This analysis involves contextualizing and interpreting the data that has been collected. The data are presented in this article in a narrative and descriptive format. The conclusion of this study on child rearing in the Islamic worldview is that raising children in the Islamic worldview is the duty of every parent. Children are a gift of Allah SWT to all parents and raising children in an Islamic perspective is an irreplaceable obligation of every parent. There are different ways of raising children in Islam, for example. How to teach the basics of Islam, give nicknames to children with good intentions, give affection every day and teach children to pray since childhood. Environmental factors, parental character and social environment can affect a child's education in Islam. How to teach the basics of Islam, give nicknames to children with good intentions, give affection every day and teach children to pray since childhood. Environmental factors, parental character and social environment can affect a child's education in Islam. The influence of raising children in Islam is to raise children with good morals and behavior, able to be filial and respect for parents, so that they become righteous and pious children.